White pole dilemma in James Baldwin`s "Another Country" - Łobodziec, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In his essay collection entitled "The Cross Of Redemption", James Baldwin pens, "There are Poles: in Warsaw (where they would like us to be friends) and in Chicago (where because they are white we are enemies). [?] It bears terrifying witness to what happened to everyone who got here, and paid the price of the ticket. The price was to become <white>. No one was white before he/she came to America".
Keywords: cultural identity; racial identity; racial consciousness; Polish-American; American city